A função do agendamento entre duas olimpíadas: os jogos olímpicos de Beijing e do Rio de Janeiro - Ni, Sen (2012)
Today, China is a country well known and unknown, a big nation of Asia and the most populous of the Earth. However, although have a history dating back thousands of years, China is also an unknown country for most of the world. But because of the Olympic Games of 2008, China became famous. In this study, propose to discuss the origin of the games what the word game means? And what is the definition. For this purpose, we use the authors as Huizinga and speak in his book that the game is a function of life, but is not capable of exact definition in logical, biological or aesthetic terms. As we know in antiquity, in most of games, a competition was devoid of objective, but as the game and culture of competition were developed, the objective of game became stronger. Because of these characteristics and the appearance of the Olympic Games, we find relevant to study the culture that emerges from jokes.